Potentiometric and UV Spectral Studies of Binary and Ternary Complexes of Some Metal Ions with N-Acetylcysteine and Amino Acids - Shaesta Quyoom; Badr-Ud-Din Khan (E-Journal of Chemistry)
The formation constants of the binary 1:1 and 1:2 complexes of Cu(II), Zn(II), Cd(II), Hg(II), and Pb(II) with N-acetylcysteine (NAC) and 1:1:1 ternary complexes of the said metal ions with NAC as a primary ligand and some biologically important amino acids as secondary ligands have been determined potentiometrically in aqueous medium. Acid dissociation constants of the ligands used and the formation constants of the binary and the ternary complexes were determined at 25 °C and in ionic strength I=0.1 mol dm-3 (KNO3).The formation constants of the 1:1 complexes were found to be higher than 1:2 complexes and the metal ions follow the order Hg(II) >Cu(II) >Cd(II) >Zn(II). In addition UV-spectral studies of the NAC-Metal (II) complexes have also been conducted at appropriate pH values to give further information about the structural nature of NAC- Metal (II) complexes in aqueous medium.